1984
DOI: 10.2337/diab.33.11.1085
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Auditory Brainstem-evoked Responses in Insulin-dependent Diabetic Subjects

Abstract: Auditory brainstem-evoked responses (ABR) were recorded from the scalp of 30 normoacoustic insulin-dependent diabetic subjects, aged between 15 and 41 yr (29 +/- 7 yr). Three different stimulus repetition rates (11, 37, and 87 cps) were used. The results were compared with those obtained from 20 age- and sex-matched, normoacoustic control subjects. In diabetic patients, metabolic control (mean daily plasma glucose, glycosylated hemoglobin) and the presence of retinopathy, nephropathy, and somatic neuropathy we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 0 publications
4
12
0
Order By: Relevance
“…A substantial delay of interpeak latency III-V shows that the diabetic neuropathy is at upper brain-stem level. These findings are similar to Durmus et al [15,18] It seems that ABR test should be a complementary diagnostic tool for early diagnosis of any auditory alterations and periodic evaluation in of diabetes for early intervention regarding metabolic regulations. of peripheral transmission time (wave I) in the auditory nerve that occurred secondary to diabetic neuropathy.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A substantial delay of interpeak latency III-V shows that the diabetic neuropathy is at upper brain-stem level. These findings are similar to Durmus et al [15,18] It seems that ABR test should be a complementary diagnostic tool for early diagnosis of any auditory alterations and periodic evaluation in of diabetes for early intervention regarding metabolic regulations. of peripheral transmission time (wave I) in the auditory nerve that occurred secondary to diabetic neuropathy.…”
Section: Resultssupporting
confidence: 90%
“…[17] The delay in inter peak latencies I-III and I-V are evidence of central conduction delay in the auditory pathway of diabetics at the level of brain-stem and mid-brain. This delay in latency for wave III and V in diabetics indicates neuropathy at brain-stem and mid-brain level in the auditory pathway Fedele et al [18] In the present study, hearing was evaluated in type 2 DM patients. Similar studies have been conducted on type 1 DM.…”
Section: Discussionmentioning
confidence: 97%
“…Fedele et al . [8] recorded BERA from scalp of 30 normoacoustic insulin-dependent diabetes subjects and found peripheral transmission time (wave I) and central transmission time (wave I-V) to be delayed. Goldsher et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies found changes in the early conponents of the ABR (21,22,24,26), while others described deficits in more central components (25,27). These functional reports support studies which have shown cranial nerve demyelination (29)(30)(31) and hearing deficits (31,32) in diabetic patients.…”
Section: Discussionmentioning
confidence: 60%
“…There are several clinical reports of deficits in the ABR of diabetics (21)(22)(23)(24)(25)(26)(27). Some of these studies found changes in the early conponents of the ABR (21,22,24,26), while others described deficits in more central components (25,27).…”
Section: Discussionmentioning
confidence: 93%